The co-design approach in the MIWOCA project. (13th November 2019) - Frahsa, A; Farquet, R; Abel, T
Abstract: : MIWOCA study group Background: The project MIWOCA researches how chronically ill women of Portuguese, Turkish and German origin and women without a migration background subjectively experience, understand, interpret and use the Swiss health care system. Methods: We conducted 48 qualitative semi-structured interviews with chronically ill women between the ages of 23 and 85 in Bern and Geneva (n = 36 with German, Portuguese and Turkish migrant backgrounds) and n = 12 Swiss women. In addition, n = 12 stakeholder interviews were conducted (doctors, nurses, social workers, psychologists, physiotherapists). In focus groups with interviewed women in Bern and Geneva, results are reflected back, identified topics from the interviews prioritized and representatives named for the cooperative planning. In a participatory planning approach, affected women in the canton of Bern, together with stakeholders from the Swiss healthcare system selected by a systematic stakeholder analysis (e.g. Swiss Medical Association, Red Cross Switzerland, Spitex, Federal Office of Public Health), develop recommendations for improving the quality of care and concrete dissemination strategies. Results: Interviewees had multiple and chronic diseases and resulting extensive experience with the Swiss healthcare system. Relevant aspects referred to issues such as quality of specific services, complexity of the healthcare system, costs of care, role of family and social support, and multidimensional stigmatization (migration, chronic illness, alleged overuse of the care system). Findings are incorporated in evidence briefs and narrative stories for focus groups and participatory planning. Conclusions: MIWOCA contributes to a targeted and differentiated improvement of structures and options for action in health care for specific groups. Results will be relevant for planning in the health system and may be incorporated into academic teaching and practical training in PH, medicine and social sciences.